Investigation and Analysis of the Development Status of Industrial Robot of China - Fangfang Li; Qian Sun (Jixie chuandong)
Industrial robot is an outstanding representative of modern new industry, a concentrated expression of advanced productivity, and also a new engine for China to enter the new normal economy and take off the economy. The technological development process of industrial robots is summarized，the current status of industrial sales at home and abroad are summarized and surveyed in detail, and the encouraging situation of the increasing sales ratio of our robot in the world is mainly introduced. The future development is looked forward, and the problem of technical support and industrial expansion of Chinese products are summarized. In the light of the new era's policies at home and abroad and the environment of production and research, some suggestions are put forward.